2022
DOI: 10.1017/s0025315422000923
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of the endangered limpet Patella ferruginea in the Chafarinas Islands (SW Mediterranean)

Abstract: The recruitment of the endangered limpet Patella ferruginea in the Chafarinas Islands (SW Mediterranean) was studied over a 17-year period (1999‒2015). A total of 8115 recruits <20 mm in maximum diameter were counted in 95 transect censuses sampled during the study period. The presence of recruits began at the end of winter or beginning of spring (March‒April), when they reached a maximum shell diameter (MD) of at least 4 mm, with a peak in abundance occurring in spring. Smaller recruits were found on the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…For instance, Ribeiro [90], in a study on dispersal and connectivity of some European limpet species in relation to the general system of currents, estimated that larval dispersal can exceed 200 km, although the number of larvae decreased sharply with distance, and Sá-Pinto et al [91] pointed out that the duration of the larval stage of related Patella species P. ulyssiponensis and P. rustica can be up to 35.5 days. Furthermore, as Guallart et al [57] noted, some isolated specimens of P. ferruginea have been found more than 200 km away from established populations, such as in the Hormigas Islands (eastern Spain) [28,92] and Liguria (north-western Italy) [30], evidence potential sporadically long-distance dispersal events in this species. Although we report a substantial percentage of self-recruitment in the analysed populations, as also observed by Cossu et al [56], 35.5% of the individuals were recognised as migrants.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…For instance, Ribeiro [90], in a study on dispersal and connectivity of some European limpet species in relation to the general system of currents, estimated that larval dispersal can exceed 200 km, although the number of larvae decreased sharply with distance, and Sá-Pinto et al [91] pointed out that the duration of the larval stage of related Patella species P. ulyssiponensis and P. rustica can be up to 35.5 days. Furthermore, as Guallart et al [57] noted, some isolated specimens of P. ferruginea have been found more than 200 km away from established populations, such as in the Hormigas Islands (eastern Spain) [28,92] and Liguria (north-western Italy) [30], evidence potential sporadically long-distance dispersal events in this species. Although we report a substantial percentage of self-recruitment in the analysed populations, as also observed by Cossu et al [56], 35.5% of the individuals were recognised as migrants.…”
Section: Discussionmentioning
confidence: 85%
“…This suggests that relevant differences in larval development and duration of pelagic phase among these species are not expected, and as such, these traits cannot be considered a biological constraint for the ferruginous limpet. Considering a planktonic larval phase of 3 to 7 days in P. ferruginea [31], Guallart et al [57] suggest that the main "hotspots" in the SE Alboran Sea, separated by a distance of about 100 km or less, could facilitate connectivity among the North African populations, depending on the environmental conditions, which may vary from year to year. Interestingly, Ferranti et al [41] found that, in the laboratory, settlement may occur up to 40 days after fertilisation in P. ferruginea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive mode seems to be even more complex, since Guallart et al (2020) observed that some 2-year-old specimens obtained in the laboratory cultures were first identified by biopsy as females-biopsy was not performed at 1 year old because they were still very small, around 25 mm MSD, and a biopsy could be lethal; and Guallart & Acevedo (2006) have suggested that sexual maturity is reached at 2 years old. These observations, despite being based on a study of P. ferruginea reproduction under controlled conditions, suggest that the species may sometimes sexually mature initially as females.…”
Section: Discussionmentioning
confidence: 99%